2005
DOI: 10.1002/jbm.b.30463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light‐cure time of adhesive resin on the thickness of the oxygen‐inhibited layer and the microtensile bond strength to dentin

Abstract: A thick oxygen-inhibited layer (OIL) on a cured adhesive layer (AL) is believed to result in both good adaptation of composite resin (CR) and high bond strength. A high degree of conversion (DC) of the AL is also needed for durable bonding. This study evaluated the hypothesis that increasing the DC by prolonging the light-curing time of adhesive bonding resin might decrease the bond strength of the adhesive to dentin because of the subsequent thinning of the OIL thickness. The OIL thickness and the DC of solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 40 publications
(134 reference statements)
2
34
0
3
Order By: Relevance
“…This fact might be due to its composition of nanosilica and nanoagglomerated zirconia fillers. The fluorescence of restorative materials has been reported to be nonstable with aging 19 ; thus, bleaching therapies might speed the aging process of restorative materials, and this may explain the observed results. Fluorescence has been shown to be dependent on the type of tested materials and, consequently, on their composition.…”
Section: Discussionmentioning
confidence: 86%
“…This fact might be due to its composition of nanosilica and nanoagglomerated zirconia fillers. The fluorescence of restorative materials has been reported to be nonstable with aging 19 ; thus, bleaching therapies might speed the aging process of restorative materials, and this may explain the observed results. Fluorescence has been shown to be dependent on the type of tested materials and, consequently, on their composition.…”
Section: Discussionmentioning
confidence: 86%
“…Some previous studies suggested a positive correlation between the presence of an oxygen-inhibited layer and composite bonding 7,8) , whereas others reported no significant differences 9,10) or even a negative correlation 11) . The presence of an adequately thick oxygen-inhibited layer was reported to be necessary for the bonding of resin composites to adhesive resins 12) . Although excessive light irradiation of the adhesives tended to increase the degree of conversion, it decreased the thickness of the oxygeninhibited layer, leading to lower bond strength to tooth substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the depth of curing and degree of conversion were statistically lower in the low-shrinkage (silorane) composites than in the conventional (methacrylate) composites (Kusgoz et al, 2011). Thus, as the polymerization of the subsurface is related to adhesive bonding strength (Kim et al, 2006), lower values can be expected with low-shrinkage resins (Guiraldo et al).…”
Section: Discussionmentioning
confidence: 99%